2007
DOI: 10.4049/jimmunol.178.2.1164
|View full text |Cite
|
Sign up to set email alerts
|

MyD88-Dependent and MyD88-Independent Pathways in Synergy, Priming, and Tolerance between TLR Agonists

Abstract: TLRs sense components of microorganisms and are critical host mediators of inflammation during infection. Different TLR agonists can profoundly alter inflammatory effects of one another, and studies suggest that the sequence of exposure to TLR agonists may importantly impact on responses during infection. We tested the hypothesis that synergy, priming, and tolerance between TLR agonists follow a pattern that can be predicted based on differential engagement of the MyD88-dependent (D) and the MyD88-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
265
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(284 citation statements)
references
References 51 publications
15
265
1
3
Order By: Relevance
“…Indeed, simultaneous targeting of the MyD88-dependent TLR9 pathway by CpG 1668 and the MyD88-independent TLR3 pathway by poly(I:C), synergistically induced IFN␤ expression in BMM⌽s. Similar effects were reported for IL-6 and TNF production after in vitro stimulation of murine M⌽s with poly(I:C) and B-type CpG ODN (22), or after in vivo challenge with the MyD88-independent TLR3 agonist poly(I:C) and the MyD88-dependent TLR2 agonist Pam3Cys (23). However, inhibitory effects on IFN␤ production were shown for poly(I:C) and CpG 2216 in BMM⌽s and CpG 2216 and R848 in BMDCs, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, simultaneous targeting of the MyD88-dependent TLR9 pathway by CpG 1668 and the MyD88-independent TLR3 pathway by poly(I:C), synergistically induced IFN␤ expression in BMM⌽s. Similar effects were reported for IL-6 and TNF production after in vitro stimulation of murine M⌽s with poly(I:C) and B-type CpG ODN (22), or after in vivo challenge with the MyD88-independent TLR3 agonist poly(I:C) and the MyD88-dependent TLR2 agonist Pam3Cys (23). However, inhibitory effects on IFN␤ production were shown for poly(I:C) and CpG 2216 in BMM⌽s and CpG 2216 and R848 in BMDCs, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…We found that LPS in the concentration range of 3-30 pg ⁄ ml, recapitulated some effects of adiponectin including attenuation of TNF induction by LPS after adiponectin pre-incubation (Fig. 1), heterologous desensitization of TLR signalling [35], as has been previously described for adiponectin by other authors [24] (Table 2), as well as direct induction of TNF-a and IL-6 and activation of p38 MAPK and nuclear factor-jB signalling (Figs. 2 and 3).…”
Section: Discussionmentioning
confidence: 57%
“…In a murine model of SLE, the genetic loss of TLR7 ameliorated disease, decreased lymphocyte activation and reduced serum IgG (16). These findings prompted us to hypothesize that repeated stimulation with a synthetic TLR7 agonist, at well tolerated low doses (10,17,18), might also restrain autoimmune inflammation.…”
mentioning
confidence: 99%